Estimation of medical radionuclide yields in photonuclear production - Dikiy, N.P.; Dovbnya, A.N.; Nikiforov, V.I.; Uvarov, V.L. (Вопросы атомной науки и техники, 2006)
The present paper reports the results from computer simulation of the processes of radionuclide production,
namely, Sc-47, Co-57, Cu-67, Mo-99, Pd-103, In-111, W-181 and Ir-192. Consideration was given to a simplified
2D-geometry version of the target device that includes a 4 mm thick tungsten bremsstrahlung converter and a cylindrical
target of natural isotopic composition that follows the converter. Radionuclide yields (gross and specific activities)
were obtained as functions of electron energies (30 to 100 MeV) at an accelerator current of 200 μA. В сообщении приведены результаты компьютерного моделирования процессов фотоядерной наработки радионуклидов Sc-47, Co-57, Cu-67, Mo-99, Pd-103, In-111, W-181 и Ir-192. Рассмотрен упрощенный вариант 2D-геометрии мишенного устройства, включающий конвертер тормозного излучения из вольфрама толщиной 4 мм и размещенную за ним цилиндрическую мишень природного изотопного состава. Получены зависимости выхода радионуклидов от энергии электронов (30…100 МэВ) при величине тока ускорителя 200 мкА. У повідомленні приведені результати комп'ютерного моделювання процесів фотоядерного
напрацювання радіонуклідів Sc-47, Co-57, Cu-67, Mo-99, Pd-103, In-111, W-181 і Ir-192. Розглянуто
спрощений варіант 2D-геометрії мішеного пристрою, що включає конвертер гальмівного випромінювання з
вольфраму товщиною 4 мм і розміщену за ним циліндричну мішень природного ізотопного складу.
Отримано залежності виходу радіонуклідів (загальна і питома активність) від енергії електронів (30…
100 МеВ) при величині струму прискорювача 200 мкА.